Radar System Development for Drone Borne Applications with Focus on Snowpack Parameters - Jenssen, Rolf-Ole Rydeng (UiT Norges arktiske universitet, 2021)
A complete representation of the Arctic cryosphere has historically been restricted by its remoteness, large extent, and restrictions in measurement methods and equipment. Here, remote sensing of snow-cover is a central method to improve the current knowledge of the Earth's ecosystem, and hence a critical component in cryospheric models. The use of drone-borne radar systems has seen considerable advances over recent years, allowing for the application of drone-mounted remote sensing of snow properties. This thesis describes the development of an ultra-wideband radar system for drone-mounted snow measurements. From the initial testing and technical implementation to field trials and method development for more advanced radar data analysis. This involves the development of lightweight and high-bandwidth radar systems intending to understand the limitations of design parameters for drone-borne radar systems and how these parameters influence the ability to measure snow conditions. Such understanding includes antenna theory and ultra wide-band radar theory, where most choices involve compromises. Snow as an electromagnetic propagation medium is presented with a focus on the previous design solutions. In that respect, various methods to measure snow parameters are discussed. Furthermore, this thesis aims to describe the iterative process of a drone-borne radar system development and how experiences from field trials are central to further improvements.